A New Look at Kant’s Genius: a Proposal of a Multi- componential Account - Jovanović, Iris Vidmar (Con-Textos Kantianos. International Journal of Philosophy, 2020)
As numerous scholars pointed out, Kant’s account of genius suffers from internal inconsistency, primarily due to the contradictory way in which Kant talks about the relation between imagination and taste in artistic production. What remains unclear is whether taste and genius work in concord in order to produce beautiful art, or whether one or the other takes charge. In this paper I look at this challenge, and I offer an interpretation of how Kant conceives of genius. I argue that the gift of genius is multi-componential, including the capacity to maximize imagination’s productivity as well as the capacity to develop taste to the point where one can extract the rules for art production, internalize them and implement them in one’s own original and exemplary artistic production. By analyzing specific claims Kant makes in relation to beautiful art, primarily his account of poetry, I extrapolate further aspects of artistic genius, which relate to his capacity to create artworks imbued with moral and cognitive significance, and which enable the awakening of genius in other artists.